The Impact of Employee Engagement, Job Satisfaction, and Compensation and Benefits towards Gen Z’s Employee Performance in PT. XYZ - Fernando, Nathaniel; Zuraida, Umi (Journal Integration of Management Studies, 2023)
PT. XYZ is a pioneer in the travel agency, and their primary goal is to reduce the time and complexity of traveling. As a company that consistently improving their human resource management system, it is considered that in order for a firm to excel in employee performance, it must guarantee high levels of employee engagement, job satisfaction, compensations and benefits, particularly for the Gen Z, the incoming generation of workers who will soon hold the majority position in the emerging labor force. This study will attempt to pinpoint and analyze the relationship and influence between employee engagement, job satisfaction, and compensation and benefits in relation to Gen Z workers' productivity on PT. XYZ. Data for this study will be collected from 63 respondents, selected from PT. XYZ Gen Z employees from various directorates with the minimum requirements of having a bachelor degree who have met the company's requirements for employee performance. This research will use a quantitative approach through a shared questionnaire. For the data analysis, the method of multiple linear regression will be used, using the SPSS tools to analyze the data. According to the study, PT. XYZ's Gen Z employees' performance is not positively and significantly impacted by employee engagement, job satisfaction, and compensation and benefits when these factors are considered separately. Instead, these factors must be combined as a whole to have a significant impact on employee performance. With the help of these insights, PT. XYZ may take the necessary action to ensure that staff performance is maximized.